2016
DOI: 10.18632/oncotarget.9706
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed profiles of lncRNAs and circRNAs with associated co-expression and ceRNA networks in bladder carcinoma

Abstract: Accumulating evidences indicate that long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) play important roles in tumorigenesis. However, the mechanisms remain largely unknown. To explore lncRNAs and circRNAs expression profiling and their biological functions in bladder cancer, we surveyed the lncRNA/circRNA and mRNA expression profiles of bladder cancer and para-cancer tissues using microarray for four patients. Thousands of significantly changed lncRNAs and mRNAs as well as hundreds of circRNAs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
188
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 38 publications
9
188
0
Order By: Relevance
“…Similarly, cir-ITCH inhibits the proliferation of ESCC by sponging miR-7, miR-17 and miR-214. To date, only two studies [30, 31] have revealed the altered expression of circRNAs in bladder cancer, indicating that circRNAs play important roles in the development and progression of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cir-ITCH inhibits the proliferation of ESCC by sponging miR-7, miR-17 and miR-214. To date, only two studies [30, 31] have revealed the altered expression of circRNAs in bladder cancer, indicating that circRNAs play important roles in the development and progression of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been experimentally validated that lncRNAs are involved in the etiology and pathogenesis of various cancers, including BLCA [13][14][15][16][17][18][19][20]. The recent advances in high-throughput data technologies, including RNAsequencing and microarrays, has guided the identification of lncRNAs for prospective clinical application in BLCA [12,[21][22][23]. However, most previous studies focused on the clinical value of individual lncRNAs, which has limited potential for future clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The ceRNA network was constructed as follows: we initially selected the DE lncRNAs and mRNAs in microarray data, and the expressions of these molecules in ESP-induced macrophages and M1 macrophages were comfirmed by qPCR, respectively. Based on the qPCR results and the screening parameter (fold change of ≥2.0 and P value<0.05), the dysregulated lncRNA or mRNA was used to perform miRNA target prediction using the latest miRBase, which collects abundant miRNAs and is extensively used as miRNA reference [41][42][43]. The obtained miRNAs were screened by miRanda and TargetScan programs.…”
Section: Rna Isolationmentioning
confidence: 99%